Quantification, Sources, and Control of Ammonia Emissions in the Czech Republic - Marie Skybova (The Scientific World Journal)
The exact quantification of ammonia (NH3) emissions is the basic presumption for the fulfilment of obligations set by the CLRTAP (Convention on Long Range Transboundary Air Pollution) Protocol which was signed by the Czech Republic in 1999. Most NH3 emissions in the Czech Republic are produced during the breeding of cattle, pigs, and poultry; therefore, determinating emission factors for these kinds of animals by studying their total number, type of breeding, and subsequent disposal of manure is the solution to the problem of NH3 emissions quantification. This paper summarizes the results of 4 years of research in this area, determining the emission factors and ways of decreasing emissions from the breeding of cattle, pigs, and poultry.